PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN DALAM PRAKTEK DI PENGADILAN AGAMA KELAS IA KOTA PADANG (STUDI KASUS NO. 166/Pdt.G/2009/PA.Pdg) - , Fahmirizal, Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to determine the legal consequences arising from the divorce of the joint property, knowing the implementation of the division of community property by divorce on the Religious Padang, revealing the obstacles encountered in implementing the division of joint property in the city of Padang and the religious court remedies. Approximation method used is an empirical approach that the authors sought judicial approach to the problems examined in accordance with the nature of the real law in force in the community. Sample collection techniques in the form of purposive sampling is based on a specific purpose. The analysis results are used is a qualitative analysis. Based on the research results can be stated that: (1). Legal consequences arising from the divorce of the joint property, namely that after the marriage the property obtained from either the husband or wife becomes joint property to the extent not otherwise provided in the covenant of marriage and if the marriage broke up, each entitled to Â½ (half) of such property (2). Division of matrimonial property on the basis of Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law, the assets acquired from either the husband or wife to be together all the rights are not otherwise provided in the marriage covenant and if the marriage broke up, each eligible 1/2 (half) of the property, as long as there is a community property marriage. (3). Obstacles that often arise in the implementation of the division of joint property is not ikhlasnya one hand, joint property is not located in one place, the evidence is incomplete. How to overcome these obstacles Clerk submit a letter of request for assistance of local checks (decente) to the Religious dispute in which the goods are located, to sell the disputed parcels of land by consent of both parties and split the proceeds equally.